Análise de observação do ensino de Libras como L1 e L2 - Sena, Caroline Costa de (Brasil, 2023)
The supervised internship aimed to bring the licentiate experience to pedagogical practice in teaching Libras as L1 for deaf people. Eleven classes were attended by eleven different teachers. Bringing unique experiences, methodologies and perspectives, as needed, were made with the understanding of past knowledge contributing to the formation of the future teacher. In addition, as collected during the internship, they were organized in the logbook, followed by the Regency with the theme The parameters of Libras. Thus, the supervised internship, especially in the current situation and the way it was taught, brought great learnings in several educational areas at Libras. For the L2 Internship, the classes were observed at the teaching institution Centro de Educação Tecnológica do Amazonas - CETAM. The group studied the intermediary Libras course, six classes were observed, with the aim of analyzing and understanding the methodologies of teaching Libras as L2. Thus, after the appropriate appropriations, they took place as class regency, bringing the theory acquired into the classroom and the practice carried out in the internship. The classes were of great teaching for the interns there, issues such as: How to take the class with hearing students and a deaf person, how to mediate with an educational purpose, the methodologies that have been perpetuated for years in the teaching of Libras.